2020
DOI: 10.7554/elife.57458
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of gaze control during prey capture in freely moving mice

Abstract: Many studies of visual processing are conducted in constrained conditions such as head- and gaze-fixation, and therefore less is known about how animals actively acquire visual information in natural contexts. To determine how mice target their gaze during natural behavior, we measured head and bilateral eye movements in mice performing prey capture, an ethological behavior that engages vision. We found that the majority of eye movements are compensatory for head movements, thereby serving to stabilize the vis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
112
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(124 citation statements)
references
References 45 publications
10
112
2
Order By: Relevance
“…1 A ). Flash duration was close to the typical fixation duration in “saccade-and-fixate” gaze patterns observed in freely moving mice ( Meyer et al, 2020 ; Michaiel et al, 2020 ). To analyze ganglion cell responses in relation to the signal inside the RF, we determined the RFs (including center and surround) from responses to spatiotemporal white noise ( Fig.…”
Section: Resultssupporting
confidence: 76%
“…1 A ). Flash duration was close to the typical fixation duration in “saccade-and-fixate” gaze patterns observed in freely moving mice ( Meyer et al, 2020 ; Michaiel et al, 2020 ). To analyze ganglion cell responses in relation to the signal inside the RF, we determined the RFs (including center and surround) from responses to spatiotemporal white noise ( Fig.…”
Section: Resultssupporting
confidence: 76%
“…Tracking these serrations allows torsional position to be determined without the use of more invasive techniques, such as limbal markings (Shen et al, 2010 ), scleral search coils (Robinson, 1963 ), or other magnetic implants (Schwarz et al, 2013 ). Our initial design used a collimating lens as shown in Figures 3A , 4A , which was subsequently adopted by others (Michaiel et al, 2020 ). We have since found that this lens is unnecessary for capturing all eye movements, and is not included in the final design ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…37 Dark stimuli that drift or loom in binocular visual space elicit freezing versus fleeing, 35,38 and mice also use binocular vision for depth perception, 34 daytime foraging, 39,40 and insect hunting. [41][42][43] Even while stationary, mice use binocular vision with greatest perceptual sensitivity, 44 but attention can quickly improve sensitivity to stimuli in monocular visual space. 45 Thus, mice show several specializations in spatial visual processing and behavior, [45][46][47] including spatially biased ON/OFF processing as shown here.…”
Section: Spikes In Lgn Show Similar Spatial Biases In On/off Responses As Those In V1mentioning
confidence: 99%